Subsídios para o manejo participativo da pesca artesanal da manjuba no Parque Estadual da Ilha do Cardoso, SP - Cardoso, Thaís Almeida (2004)
The manjuba small-scale fishing, also known as "iriko" fishing, is a common "caiçara" practice which has been present in Cardoso Island for approximately seventy years. The need to study this kind of fishing results from restrictions to this activity imposed by the legislation, due to the small mesh of the nets used. This work was developed in the Enseada da Baleia and Vila Rápida communities with the aim of obtaining subsidies for the comanagement of manjuba fishing. Human Ecology and Ethnoecology approaches were used as the research leading line, and the following methodological procedures were used: open or free interviews, direct observation, life history, quizzes for production results, fishing efforts, and accompanying fauna . Data about the technique and strategies used in the manjuba fishing and about the studied fishermen local knowledge, including the ethnobiological classification of manjuba, were obtained, and the social, ecological and economical aspects involved in this type of fishing were analyzed. It was noticed that the fishermen s knowledge and experience as well as the fishing gear limitations are important for the execution of more selective fishing and for the conservation of the resource. However the lack of current studies about the manjuba stock in the region hinders the analysis of the production data obtained from the point of view of its sustainable exploitation. It was observed that industrial fishing, official control and restricted market are the main external factors that directly interfere in the fishing activity studied here. Some proposals were suggested for the management of manjuba fishing, highlighting the need of performing this activity with the participation of the communities who are users of this resource. It is important to obtain alternative forms of uses and management of natural resources which should be ecologically and socially appropriate starting from the dialog and knowledge integration between researchers, public institutions and human groups studied.